2008
DOI: 10.1007/s11244-008-9121-0
|View full text |Cite
|
Sign up to set email alerts
|

Deactivation, Regeneration, and Stable Performance of a PtMoRe Water Gas Shift Catalyst for On-Site Hydrogen Generation: Part 2

Abstract: This paper analyzes the mechanism of deactivation and methods of regeneration of a PtMoRe water gas shift catalyst supported on a stabilized zirconia. Although this catalyst initially possesses high activity below 250°C, a decrease in CO conversion ranging from 10 to 50% was observed over a period of 60 h. To determine the mechanism responsible for the decay, a series of activity tests and high resolution transmission electron microscopy analyses were done. Experimental results revealed the existence of stable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Thus, Mo and MoOx could have a role in improving the catalytic performance of Pt-based catalysts for the WGS reaction. Dorazio et al [17,18] found that Mo-promoted Pt catalysts were highly active in the WGS reaction and the formation of the PtMo alloy was essential to the high activity. Williams et al [19] studied the effect of Mo addition on supported Pt catalysts in the WGS reaction and found that reducible Mo oxide in close proximity to Pt enhanced the reaction rate.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Mo and MoOx could have a role in improving the catalytic performance of Pt-based catalysts for the WGS reaction. Dorazio et al [17,18] found that Mo-promoted Pt catalysts were highly active in the WGS reaction and the formation of the PtMo alloy was essential to the high activity. Williams et al [19] studied the effect of Mo addition on supported Pt catalysts in the WGS reaction and found that reducible Mo oxide in close proximity to Pt enhanced the reaction rate.…”
Section: Introductionmentioning
confidence: 99%